Equity home bias in the Czech Republic - Karel Báťa (Charles University in Prague, Institute of Economic Studies (IES), 2010)
Investors reveal a tendency to prefer domestic over foreign equities despite the financial losses. From institutional perspective the factors that cause home biasness are the barriers to entry the foreign markets, transaction costs, illiquidity, asymmetric information and information costs, corporate governance and inflation and exchange rate risks. Behavioral finance argues that irrationality of investors cause the home biasness. Investors tend to be under the influence of psychological biases: optimism, overconfidence, social identity, narrow framing and loss aversion. In this paper we introduce a model of optimal portfolio of Czech investors with three utility functions: Markowitz, exponential and CRRA. The prediction of the model without short selling suggests that Czech investors should have more than 60 % (between 72 - 83 % for feasible levels of risk aversion) in domestic equities. The OECD data claims that they hold around 87 % in domestic equities.
Keywords: G11; 330; equity home bias; optimal investment portfolio; behavioral finance; Home Bias Puzzle; Anlageverhalten; Portfolio-Management; Tschechische Republik